DISINFORMATION AND THE FRAGILITY OF DEMOCRACY IN THE DIGITAL AGE: THE CHALLENGES OF THE BRAZILIAN ELECTORAL SYSTEM (CIPEEX, 2025)
The influence of digital technologies on political social relations has been transforming the way information circulates, especially during election years. In this context, disinformation, spread in a disorderly manner, reaffirms the challenge to the democratic objectives of our society. This study aims to analyze the impacts of disinformation and digital electoral crimes within democratic processes, highlighting the 2018 and 2022 elections. It also involves qualitative, bibliographical, and scientific research, based on legislation such as the Internet Civil Rights Framework and the Election Law, as well as documented analysis and decisions issued by the Superior Electoral Court (TSE). The data analyzed during its execution indicate that, although measures have been taken to mitigate its negative effects, regulatory and operational gaps remain that tend to hinder the fight against fake news. This study showed us that this challenge requires repressive and educational actions from everyone—the government and society—aimed at developing critical and conscientious citizens. Protecting the electoral process involves building defense mechanisms that value truth as the foundation of the laws that lead us to true democracy.
Keywords: Democracy; fake news; Electoral law; disinformation